Analisis Berpikir Intuitif Siswa SMP dalam Pemecahan Masalah Bangun Datar Berdasarkan Gaya Belajar - Dwi Wulandari; Dian Septi Nur Afifah (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the intuitive thinking skills of junior high school students in solving geometric problems based on their learning styles: visual, auditory, and kinesthetic. The research employed a descriptive method with a qualitative approach. Data were collected through a learning style questionnaire to categorize students, problem-solving tests on geometric shapes, and in-depth interviews to explore students' intuitive thinking abilities. The findings indicate that students with a visual learning style exhibit stronger intuitive thinking skills compared to those with auditory and kinesthetic learning styles. Visual learners provided clear and well-structured answers aligned with intuitive thinking indicators such as Catalytic Inference, Power of Synthesis, and Common Sense. Conversely, auditory learners tended to give less detailed answers, although they could identify relevant information. Kinesthetic learners offered brief and less detailed responses, particularly in specifying measurements and units in their calculations. These findings underscore the importance of understanding students' diverse learning styles to optimize mathematics teaching strategies, particularly in enhancing problem-solving skills and intuitive thinking.